2023
DOI: 10.1136/bjo-2022-322979
|View full text |Cite
|
Sign up to set email alerts
|

Variability of scan quality and perfusion density in longitudinal optical coherence tomography angiography imaging

Corey A Smith,
Vanessa L Josey,
Michael E West
et al.

Abstract: Background/aimsOptical coherence tomography angiography (OCT-A) images are subject to variability, but the extent to which learning impacts OCT-A measurements is unknown. We determined whether there is a learning effect in glaucoma patients and healthy controls imaged with OCT-A.MethodsNinety-one open-angle glaucoma patients and 54 healthy controls were imaged every 4 months over a period of approximately 1 year in this longitudinal cohort study. We analysed 15°×15° scans, centred on the fovea, in one eye of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…The VLD is defined as the vessel length per unit area and was calculated on the skeletonized image. 18 21 Given that several studies have shown that the deep FAZ has less well-defined borders than the superficial FAZ, 22 , 23 we computed the FAZ area (in mm 2 ) using the binarized superficial en face OCTA slab only 22 , 23 ( Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The VLD is defined as the vessel length per unit area and was calculated on the skeletonized image. 18 21 Given that several studies have shown that the deep FAZ has less well-defined borders than the superficial FAZ, 22 , 23 we computed the FAZ area (in mm 2 ) using the binarized superficial en face OCTA slab only 22 , 23 ( Fig. 1 ).…”
Section: Methodsmentioning
confidence: 99%